Tuberculosis screening during the 2015 European refugee crisis - Susanne Tewes; Bennet Hensen; Alexandra Jablonka; Dana Gawe; Maija Kastikainen; Christine Happle; Julia Carlens; Lars-Daniel Berthold; Frank Wacker (BMC, 2020)
Abstract Background The purpose of our study was to describe and evaluate management, performance and results of Tuberculosis (TB)-screening among refugees and asylum seekers in a rural area in Germany in 2015. Methods Refugees or asylum seekers, staying in shared-accommodation are obligated to participate on screening chest X-ray (CXR) in order to screen for signs of potentially infectious pulmonary TB (German Protection against Infection Act and German Asylum Procedure Act). n = 705 individuals underwent screening chest X-ray (CXR) to detect pulmonary TB in September and October 2015 on site. One experienced radiologist interpreted and reported each CXR within 24 h after the enrollment in the screening program and results were sent to the local Public Health Department for potential further medical care. Image abnormalities suggestive for TB were defined according to established radiographic criteria such as pleural effusion, cavitation, consolidation, fibrous scarring or calcification. Only in case of TB-suggestive findings on CXR, further diagnostics were arranged (pulmonological examination, follow-up CXR, sputum culture, interferon-gamma release assay, bronchoscopy). Follow-up data was collected in collaboration with the local Public Health Department. Descriptive statistics were calculated using GraphPad Prism software. Results n = 637 CXR examinations (90%) did not show abnormal findings, n = 54 CXR (8%) showed incidental findings, and n = 14 CXR (2%) were suspicious for acute TB. Of these, n = 14 individuals, eight underwent further TB diagnostics. Active TB was confirmed in one individual (0.001% of the screening cohort). Conclusions Our cohort reflects current immigrations statistics in Europe and illustrates an overall low TB prevalence amongst individuals entering Germany in 2015. However, our findings support the improvement of diagnostic algorithms.